The Calculation of meshing efficiency of a new type of conical involute gear - Li, Yu (Strojniški vestnik, 2017)
A new type of conical involute gear, proposed in this paper, can be applied in precise gear transmission for adjusting the backlash because of the special characteristics of its teeth. The meshing states of parallel external gear transmission based on the proposed gears are analysed and presented. The expressions of the length of contact and relative sliding velocity at any meshing position are derived. Then, the calculation formula of meshing efficiency is given by utilizing the piecewise equivalent method. Next, the variation of the length of contact line, unit load, meshing efficiency in a meshing period with different gear parameters and different operations are illustrated by employing numerical examples, and the influences of gear parameters and operations on meshing efficiency of the proposed gears are discussed based on the computing results. In the end, the applicability of the calculation is introduced.
Keywords: izgube zaradi drsnega trenja; mikrosegmenti; stožčasti evolventni zobniki; tangencialna modifikacija; učinkovitost ubiranja; zobniški prenosniki